Reliability and validity of the 2002 and 2006 Chapel Hill expert surveys on party positioning - Bakker, Ryan; Brigevich, Anna; Edwards, Erica; Hooghe, Liesbet; Marks, Gary; Rovny, Jan; Steenbergen, Marco; Vachudova, Milada; de Vries, Catherine (European Consortium for Political Research, 2010)
This research note reports on the 2002 and 2006 Chapel Hill expert surveys (CHES), which measure national party positioning on European integration, ideology, and several European Union (EU) and non-EU policies. The reliability of expert judgments is examined and the CHES data are cross-validated with data from the Comparative Manifesto Project, the 2003 Benoit-Laver expert survey and the 2002 Rohrschneider-Whitefield survey. The dataset is available on the CHES website.
Keywords: 59 Ciencia Política; ODS 10 - Reducción de las desigualdades